2018
DOI: 10.7762/cnr.2018.7.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-meal Water Consumption on Energy Intake and Satiety in Non-obese Young Adults

Abstract: I determined whether water consumption reduces energy intake and affects satiety in non-obese young adults. The final subjects consisted of 15 individuals (8 women and 7 men) with average ages of 26.4 and 23.5 years for women and men, respectively. When subjects drank water before eating a test meal, they ate a lower amount of the test meal compared to eating test meals under waterless and postload water conditions (preload water: 123.3 g vs. waterless: 161.7 g or postload water: 163.3 g, p < 0.05). Water cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Sufficient nutrient intake is essential to maximize subsequent exercise performance and to support training adaptations through replenishment of glycogen stores [40] and promotion of muscle protein synthesis [41]. Conversely, for someone seeking weight reduction, increasing water intake is often recommended with the rationale this could decrease energy intake at a meal and decrease hunger [42,43]. While chronic underhydration has been associated with obesity [22], other reports suggest hypohydration reduces subsequent food intake [37].…”
Section: Appetitementioning
confidence: 99%
“…Sufficient nutrient intake is essential to maximize subsequent exercise performance and to support training adaptations through replenishment of glycogen stores [40] and promotion of muscle protein synthesis [41]. Conversely, for someone seeking weight reduction, increasing water intake is often recommended with the rationale this could decrease energy intake at a meal and decrease hunger [42,43]. While chronic underhydration has been associated with obesity [22], other reports suggest hypohydration reduces subsequent food intake [37].…”
Section: Appetitementioning
confidence: 99%
“…When a person consumes water before breakfast, it will slow down gastric emptying to trigger feelings of fullness and reduce hunger. In addition, food intake will also decrease when drinking water before breakfast [13]. Water consumption can also stimulate the sympathetic nerves to increase metabolic rate, such as triggering thermogenesis and increasing energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Health experts commonly recommend consuming eight glasses of water to maintain health and well-being. Consuming more water than normally consumed at mealtimes (breakfast, lunch and dinner) under dietary recommendations can reduction in meal energy intake (Jeong, 2018). Another recommended and suggested action to maintain health and fitness is by doing physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that overweight and obese adult subjects lost weight by consuming two cups (500 mL) of plain water 1-2 hours before mealtime (lunch and dinner) (Dennis et al, 2011). Therefore, taking pre-meal water to reduce meal energy intake can be an effective weight control strategy (Jeong, 2018).…”
Section: Introductionmentioning
confidence: 99%